Fishers’ Knowledge on Marine Fisheries Management and Conservation - Shankar, S Sabari; Anand, G Ajay; Immanuel, Sheela; Vennila, A (Fishery Technology, 2025)
Marine fishers play an important role in the management of marine resources. Hence, there is a need to analyse the fishers’ knowledge level in relation to marine fisheries resource management and conservation. The present study was undertaken in selected fishing villages of Kanyakumari district of Tamil Nadu. The ‘Teacher made test’ was constructed and used for the assessment of fishers’ knowledge. More than 60% of the respondents had medium level of knowledge on marine fisheries management and conservation, marine policies and regulatory measures and mariculture practices. Fishers’ knowledge on marine parks and sanctuaries, community based approach, oil spillage, installation of artificial reefs, mesh size for catching shrimps and catching of brood fishes was found to be low. Fishers had medium level of knowledge on issues like over exploitation, mangrove destruction, marine pollution, and mesh size regulations, mechanisation of boats, indiscriminate fishing methods and fishing with nets of reduced mesh size. These areas need to be taken into account for enhancing the fishers’ knowledge level for increasing sustainability of fishing.